MOSQUITOE’S LARVAL GROWTH WITH REFERENCE TO WATER PARAMETERS IN UKKADAM PERIYAKULAM LAKE- COIMBATORE, TAMILNADU, INDIA - D, Rajmohan; R, Yamuna; K, Logankumar; M, Manimegalai; K, Sathish Kumar (Kongunadu Research Journal, 2016)
Mosquitoes lay eggs in a wide range of habitats with different physicochemical parameters. Ecological data, including physicochemical factors of oviposition sites, play an important role in integrated vector management. Those data help the managers to make the best decision in controlling the aquatic stages of vectors especially using source reduction. To study some physicochemical characteristics of larval habitat waters, an investigation was carried out in Ukkadam periyakullam lake Coimbatore. Water samples were collected during larval collection from three localities. The chemical parameters of water samples were analyzed based on mg/l using standard methods. Water temperature (°C), turbidity (NTU), total dissolved solids (ppm), electrical conductivity (μS/cm), and acidity (pH) were measured using digital testers. Thermotolerant coliforms of water samples were analyzed based on MPN/100ml. In total, 112 mosquito larvae were collected. There was no significant correlation between the abundance of larvae and the different physicochemical and microbial parameters. But fecal coliform was the major impacting factor in the study area.